Design of concrete structures for retaining aqueous liquids design tables to BS 8007 - Cheng, Richard (Thomas Telford, 1996)
Divided into two parts, this book provides calculations of minimum reinforcement, crack spacing, and crack widths in relation to temperature and moisture effects. It also provides calculations of crack widths in mature concrete under structural loading, and summarises the design formulae and tables B1 to B36 tabulate the service.